Pediatric Sellar: Suprasellar Tumors - Papadopoulou, Elissavet; Chourmouzi, Danai; Drevelegas, Antonios (Journal of Pediatric Neuroradiology, 2016)
Tumors of the sellar region are not infrequent in pediatric population and differ notably from the adult sellar tumors. Craniopharyngiomas represent almost half of sellar region tumors in children, followed by hypothalamic-chiasmatic gliomas, hypothalamic hamartomas, and germinomas. Other tumors or tumoral lesions are more infrequent. This article provides an overview of the imaging characteristics of pediatric sellar/suprasellar tumors on conventional magnetic resonance (MR) imaging that can orient the diagnosis or limit the differential diagnostic range. Furthermore, the physiologic characteristics assessed by advanced MR imaging techniques are also described in detail, providing a better preoperative characterization of pediatric sellar/suprasellar pathology.
Keywords: pediatric sellar/suprasellar tumors; craniopharyngioma; hypothalamic-chiasmatic glioma; hypothalamic hamartoma; germinoma